2021
DOI: 10.1016/j.ekir.2020.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients with End-Stage Kidney Disease in ADPKD

Abstract: Introduction Cystic expansion damaging the parenchyma is thought to lead to end-stage kidney disease (ESKD) in autosomal dominant polycystic kidney disease (ADPKD). Here we characterized genotypic and phenotypic attributes of ADPKD at time of ESKD. Methods This is a retrospective cross-sectional study of patients with ADPKD with ESKD evaluated at Mayo Clinic with available abdominal computed tomography (CT) or magnetic resonance imaging (MRI). Kidney volumes were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Therefore, discordance between cyst burden and renal function decline trajectories that could be explained by lower cyst growth and remarkably slowed kidney enlargement in this ADPKD patient. In the present study, it was hypothesized that coexisting ADPKD with masked KS and GS may have a synergistic effect on the stimulation of rapid evolution to ESRD, and their synergistic effect may be the result of regulation of multiple signaling pathways, including vascular disease [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, discordance between cyst burden and renal function decline trajectories that could be explained by lower cyst growth and remarkably slowed kidney enlargement in this ADPKD patient. In the present study, it was hypothesized that coexisting ADPKD with masked KS and GS may have a synergistic effect on the stimulation of rapid evolution to ESRD, and their synergistic effect may be the result of regulation of multiple signaling pathways, including vascular disease [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, activation of the mTOR pathway and increased vascular endothelial apoptosis in KS [66] and ADPKD could affect the intracranial aneurysm growth in our patient [23,24,67]. Finally, other possible factors that could affect ADPKD progression and the growth of the intracranial aneurysm in this patient include also an increased RAAS stimulation, apoptosis, fibrosis, and vascular disease [26,27,68]. On the other hand, in both ADPKD and KS there is an elevated frequency of intracranial aneurysms and, in the case of associated variants in PKD1 protein and KS, it is expected to have at least additive intracranial aneurysms in disease presentation [21,49,50,55].…”
Section: Co-occurrence Of Adpkd Ks and Gsmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, 50% of the patients reached ESKD by age of 54 years and 75% by age of 62 years in a recent study with a large tertiary care center cohort [ 18 ]. It has also been demonstrated that, within a family, despite shared mutations, there is wide variability in the age at which a family member reaches ESKD [ 19 ]. Given the wide heterogeneity and phenotypic variability of ADPKD, it is prudent to identify the group of patients who are at risk of rapid progression toward ESKD to initiate disease-modifying treatment early to slow the progression of the kidney disease.…”
Section: Assessment Of Risk Of Rapid Progression In Autosomal Dominan...mentioning
confidence: 99%
“…1,2 It is a phenotypically variable disease with patients progressing to kidney failure from relentless kidney growth. 3 Disease severity stratification using genetic, clinical, and radiological biomarkers is used to predict the rate of ADPKD progression. 4 Height-adjusted total kidney volume (Ht-TKV) has been recognized as a prognostic biomarker of cystic burden and disease severity.…”
Section: Introductionmentioning
confidence: 99%